PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISTIK SEBAGAI UPAYA MEMPERLUAS PEMAHAMAN PEMBACA TERHADAP TEKS NAUSI-FIKSI :Studi pada Mahasiswa Jurusan Pendidikan Bahasa dan Sastra Indonesia FiaP-Unswagati Cirebon - Abdul Rozak, - (2001)
The title of this thesis is The Applying Constructivist-learning Model as an Effort to Enlarge the Readers' understanding of Fictional Narration Text. (The Study on the Students of the Indonesian Language and Literature Education Program, FKIP Unswagati Cirebon). This research is aimed at the application of the Constructivist-learning model. The questions are: (1) how far is the teachers role in the constructivist-learning model, (2) how far activity the learners at the time they interact with the fictional narration text in the Constructivist-learning model, and (3) how far the learners schema involve at the time the learner interact with the narration-fiction text in the constructivist-teaming model This problem solving applied descriptive-qualitative research. The Constructivist-learning model was applied in the class room that had lecture of fictional prose studies. The Constructivist-learning model is a model which is based on the Constructivism-philosophy theory of Jean Piaget and literarily it applied readers response approach theory of Rosenblatt (1978, 1983) which was in future improved by Beach and Marshall (1990), Langer (1991), Probst (1987) and Dugan (1997). This theory emphasizes personal aspect in signification of the fictional narration text they read. The signification is formed by transaction process. The research data are in the form of learning activity and the result of the learning activity. The learning activity is in the form of transcript discussion and the result of the learning activity is in the form of construction which is the result of the learner reflection. Based on the data analysis, the learners construction shows that there is involvement of the scheme that they have. When they transact with the fictional narration text, the learners use their scheme as the effort of understanding. At the time of interaction and reflection, this research is aimed at the availability of the learners' efforts that match and use their scheme in forming the construction as the reflection form and in understanding the fictional narration text they read. Their activation was proved when they gave the response in the class-discussion. The writing construction (the reflection form) also shows that there is the activity in signification as the effort of understanding of the fictional narration text they read. This proves that the application of constructivist learning model is able to enlarge the learners'/readers' understanding of the fictional narration text. Constructivist learning model can be used with some requirements. Firstly, the teacher should be flexible, not authoritarian, understand the fictional prose that will be discussed and responded by the learners. Secondly, the signification must be based on the learners. The learners' responses may not which are judged as" true" or "false". Thirdly, using discussion technique. This technique enables the appearance of the learners' creativity. Furthermore, their activity will bring about immediacy and involvement in giving the response.